2013
DOI: 10.1039/c3cc43000f
|View full text |Cite
|
Sign up to set email alerts
|

Complexation with organometallic ruthenium pharmacophores enhances the ability of 4-anilinoquinazolines inducing apoptosis

Abstract: The complexation with organoruthenium fragments confers 4-anilinoquinazoline pharmacophores with higher potential for inducing cellular apoptosis while the highly inhibitory activity of 4-anilinoquinazolines against EGFR and the reactivity of the ruthenium centre to 9-ethylguanine are well preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…38,43 Then the arene-ruthenium(II) dimer complex [(η 6 -p-cymene)RuCl 2 ] 2 was reacted with ligands L1 or L2 to produce complexes 1 or 2, respectively, and [(η 6 -pcymene)Ru(en)Cl][PF 6 ] was reacted with L3 or L4 to produce complexes 4 or 5, respectively. 30 Complexes 1 -5 have a derived quinazoline group which is the active site of gefitinib. Meanwhile, they have a halfsandwich ruthenium moiety, which is broadly regarded cytotoxic.…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…38,43 Then the arene-ruthenium(II) dimer complex [(η 6 -p-cymene)RuCl 2 ] 2 was reacted with ligands L1 or L2 to produce complexes 1 or 2, respectively, and [(η 6 -pcymene)Ru(en)Cl][PF 6 ] was reacted with L3 or L4 to produce complexes 4 or 5, respectively. 30 Complexes 1 -5 have a derived quinazoline group which is the active site of gefitinib. Meanwhile, they have a halfsandwich ruthenium moiety, which is broadly regarded cytotoxic.…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
“…[6][7][8]27 For instance, the {(η 6 -arene)Ru} (arene = cyclopentadienyl, benzene, p-cymene, biphenyl, etc.) units can coordinate with ethylenediamine, imidazole, 2-(aminomethyl)pyridine, derived enzyme inhibitors to get a series of novel complexes with diverse biological activity and improved antitumour activity, 24,[28][29][30][31][32][33] indicating the possibility of organometallic ruthenium(II) arene complexes for the development of multi-functional antitumour drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4-Anilinoquinazoline moieties, derivatives of the TKI gefitinib, were complexed with Ru(II) via an amine side chain, and shown to have enhanced ability for causing cellular apoptosis [ 170 ]. This is not surprising, as several Ru II and Ru III based complexes have shown promising anticancer and antimetastasis activities [ 171 ].…”
Section: Targeting Egfr and Vegfr For Molecular Imagingmentioning
confidence: 99%
“…The aquated form of complex 8 (Figure ) binds to guanine bases in DNA with loss of aqua ligands. [39c] The arene ligands with extended ring systems, such as biphenyl moieties, were found to π‐stack with DNA bases or to intercalate partially into adjacent DNA base pairs, as observed in calf‐thymus DNA by UV/Vis spectroscopy and circular dichroism spectropolarimetry. Moreover, molecular docking studies also showed that the aquated Ru center was able to form two new hydrogen bonds in addition to the existing interactions between the organic 4‐anilinoquinazoline scaffold and the protein pocket, which would be predicted to enhance ligand binding.…”
Section: Metal Complexes As Protein Kinase Inhibitorsmentioning
confidence: 99%